Double Suppression of the G? Protein Activity by RGS Proteins. - Lin, C.; Koval, A.; Tishchenko, S.; Gabdulkhakov, A.; Tin, U.; Solis, G.P.; Katanaev, V.L. (Molecular Cell, 2014)
Regulator of G protein signaling (RGS) proteins accelerate GTP hydrolysis on G protein ? subunits, restricting their activity downstream from G protein-coupled receptors. Here we identify Drosophila Double hit (Dhit) as a dual RGS regulator of G?o. In addition to the conventional GTPase-activating action, Dhit possesses the guanine nucleotide dissociation inhibitor (GDI) activity, slowing the rate of GTP uptake by G?o; both activities are mediated by the same RGS domain. These findings are recapitulated using homologous mammalian G?o/i proteins and RGS19. Crystal structure and mutagenesis studies provide clues into the molecular mechanism for this unprecedented GDI activity. Physiologically, we confirm this activity in Drosophila asymmetric cell divisions and HEK293T cells. We show that the oncogenic G?o mutant found in breast cancer escapes this GDI regulation. Our studies identify Dhit and its homologs as double-action regulators, inhibiting G?o/i proteins both through suppression of their activation and acceleration of their inactivation through the single RGS domain.